EFFICIENCY OF COMPETITIVENESS PRIORITIES - Raja Abd. Rahman, Raja Roslan; Dora, Mohd. Taib; Rahman, Noor Watee (Journal of Human Capital Development (JHCD), 2009)
The purpose of this study was to measure the efficiency of competitiveness priorities on adoption of Electronic Procurement (e-Procurement) system to enhance service performance at Universiti Teknikal Malaysia Melaka. A survey was carried out through a set of questionnaires. The sample size is 200, but only 153 respondents participate in this survey. The staffs were from Universiti Teknikal Malaysia Melaka Durian Tunggal, Ayer Keroh and Kampus Bandar. Based on the analysis the result revealed that most of the respondents (49.7%) believed that reduction in cost such as inventory and invoice with e-Procurement. The analysis also established that most of the respondents believed that administrative tasks such as paperwork & manual filing reduce with e-Procurement (59.5%). In terms of quality, 49.7% believed that it was easier meeting the customer’s expectation towards product and services increase with e-Procurement. Thus, it showed that it was very important to meet the customer expectation and satisfaction in order to enhance the quality requirement. Apart from that, based on the response associated with competitive priorities and service performance, 67.3% of the respondents assumed that the main priority on using e-Procurement was to increase the quality service of the government sectors. The finding indicated that there was a strong positive relationship between cost (.778), time (.758) and service performance. In fact, result also showed that there was a strong positive relationship between quality (.786) and service performance. The finding also showed that there was a high association between competitive priorities (.865) and service performance. It was stated that the result accept the alternative hypothesis because there was high positive relationship between competitive priorities and service performance in UTeM. Keywords: efficiency, competitiveness priorities, adoption, e-procument system, enhance service performance